PELATIHAN BTQ MENGGUNAKAN METODE CARD SORT BAGI SANTRI RUMAH TAHFIZ FIISABILILLAH KOTA PADANG - Akhyar, Muaddyl; Kustati, Martin; Amelia, Rezki (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This training aims to improve BTQ skills for students of the fiisabilillah tahfizh house. One method that helps in reading and writing the Qur'an (BTQ) is the Card Sort method. The Card Sort method is a method using a variety of cards that will later be filled with hijaiyyah letters and their letter lines. This is done because some students often forget and are less able to write hijaiyah letters that have been taught, and they feel bored and bored with learning using reading books so that some students like to walk around, chat, draw which is not in accordance with learning to read and write the Qur'an. The implementation of this training uses a qualitative method with a PAR (Participatory Action Research) approach and uses three main pillars namely research methodology, action dimension, participation dimension. The results of using the Card Sort method, students more easily understand and remember each hijaiyah letter along with the reading line and are able to write and pronounce each hijaiyah letters that has been explained. The implementation of this training also produces a good quality of basic understanding of hijaiyah letters because in the process students tend to be more focused in listening and paying attention to the direction of the teacher. In addition, students are more excited and active in the learning process of reading and writing the Alqur'an, because the hijaiyah card media used is very interesting and different from the use of reading books. Training using this method can also be used and implemented by Tahfizh Houses in other places, because the method is very easy to use and the media is very easy to find.